2017
DOI: 10.1111/dme.13380
|View full text |Cite
|
Sign up to set email alerts
|

Older people with Type 2 diabetes, including those with chronic kidney disease or dementia, are commonly overtreated with sulfonylurea or insulin therapies

Abstract: In the present cohort of older people with Type 2 diabetes prescribed sulfonylurea or insulin therapies, overtreatment was common, even in the presence of comorbidities known to increase hypoglycaemia risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 21 publications
(30 reference statements)
2
49
0
Order By: Relevance
“…A number of RCTs have shown that intensive glycaemic control directed at lower HbA1c targets is associated with only minor cardiovascular benefits, but increased adverse events such as mortality . Evidence shows that older people with type 2 diabetes and other comorbidities are being overtreated with drugs that cause hypoglycaemia . Hambling and colleagues observed that older people, including those with comorbidities such as CKD or dementia, were managed to similar intensive thresholds as those without CKD or dementia .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of RCTs have shown that intensive glycaemic control directed at lower HbA1c targets is associated with only minor cardiovascular benefits, but increased adverse events such as mortality . Evidence shows that older people with type 2 diabetes and other comorbidities are being overtreated with drugs that cause hypoglycaemia . Hambling and colleagues observed that older people, including those with comorbidities such as CKD or dementia, were managed to similar intensive thresholds as those without CKD or dementia .…”
Section: Discussionmentioning
confidence: 99%
“…46 Evidence shows that older people with type 2 diabetes and other comorbidities are being overtreated with drugs that cause hypoglycaemia. [20][21][22]47 Hambling and colleagues observed that older people, including those with comorbidities such as CKD or dementia, were managed to similar intensive thresholds as those without CKD or dementia. 47 These older patients are especially vulnerable to hypoglycaemic episodes and other adverse events such as fractures, head injuries, CVD, or even death, 9,11,12 given predisposing factors such as advanced age, frailty, long duration of diabetes, polypharmacy, and comorbidities such as CKD and cognitive impairment.…”
Section: Implications Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Self-management of diabetes is particularly challenging for older patients because they have limited recall of the dangers of hypoglycaemia and what remedial action to take, 4 and because they are more prone to hypoglycaemia because of their medication. 5,6 The burden of hypoglycaemia in older patients has mounted steadily, [7][8][9] with one study reporting a 267% increase in hospitalizations for hypoglycaemia in patients aged 75 years or older in England and Wales (2000-2014) and a 10-fold higher admission rate compared to patients in the 15-59 years of age group. 7 A worldwide study of 109 countries revealed a 60% increase in hypoglycaemia-related deaths between 2000 and 2010, with these deaths occurring mainly in individuals over the age of 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major challenges facing current treatment strategies is that a substantial number of older patients with T2DM struggle to achieve even their less stringent individualised glycated haemoglobin (HbA1c) targets . Furthermore, many of these patients are on complex regimens that include insulin and/or a sulphonylurea (SU), drugs that increase the risk of hypoglycaemia . While metformin continues to be a first‐line medication in the treatment of T2DM, recent recommendations for the treatment of patients aged >65 years focus on regimens with either basal insulin, dipeptidyl peptidase‐4 (DPP‐4) inhibitors, or a combination of these …”
Section: Introductionmentioning
confidence: 99%